4D ultrasound study of fetal facial expressions at 20–24 weeks of gestation. Issue 3 (21st May 2014) - Sato, Miki; Kanenishi, Kenji; Hanaoka, Uiko; Noguchi, Junko; Marumo, Genzo; Hata, Toshiyuki
Abstract: Objective: To assess the frequency of fetal facial expressions at 20–24 weeks of gestation using four‐dimensional (4D) ultrasonography and to determine whether there was any correlation between facial expression and gestational age (20–34 weeks). Methods: The facial expressions of 23 healthy fetuses were examined using 4D ultrasound at 20–24 weeks. Each fetus was recorded continuously for 15 minutes. The frequencies of mouthing, yawning, smiling, tongue expulsion, scowling, sucking, and blinking were assessed and the data combined with those expressions observed at 25–34 weeks of gestation in two previous studies (n = 34) to determine the correlation between gestational age and each of the facial expressions. Results: Mouthing was significantly more frequent than the other six facial expressions at 20–24 weeks ( P < 0.05). Yawning was significantly more frequent than smiling, scowling, and blinking ( P < 0.05), and sucking was significantly more frequent than smiling, scowling, and blinking ( P < 0.05). The frequency of yawning, smiling, tongue expulsion, scowling, and blinking increased with gestational age ( P < 0.05). Mouthing movement and sucking frequencies remained constant between 20 and 34 weeks. Conclusion: Frequencies of complicated facial expressions such as smiling and scowling may increase with advancing gestation owing to the development of the fetal brain and central nervous system.